Tumpek Wariga: Integrasi Hukum Agama dan Peraturan Daerah untuk Ketahanan Pangan Lokal - Suriata, I Nengah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
This research was conducted to reveal the integration of law and Hindu religious teachings, namely tumpek wariga with Regional Regulation Number 8 of 2019 concerning Organic Farming Systems. This research is a descriptive qualitative model with data collection techniques through direct observation in the field (observation), in-depth interviews, and document searches. The results of the research show that the integration of the laws and teachings of the Hindu religion tumpek wariga and Regional Regulation Number 8 of 2019 can increase rice production in Bali, so that it can become a strategy for local food security in the Bali region. It is known that since the regulation was implemented in 2020, the amount of rice production in Bali has continued to increase. In fact, in 2023 it will be able to meet the needs of all Balinese people. In practice, this research contributes to the harmonization of the relationship between religion and the state, and theoretically there needs to be further research regarding system theory in the religious and state system more broadly. Penelitian ini dilakukan untuk mengungkap integrasi hukum dan ajaran Agama Hindu, yaitu tumpek wariga dengan Peraturan Daerah Nomor 8 Tahun 2019 tentang Sistem Pertanian Organik. Penelitian ini model kualitatif deskriptif dengan teknik pengumpulan data melalui pengamatan langsung ke lapangan (observasi), wawancara mendalam, dan penelusuran dokumen. Hasil penelitian menunjukkan bahwa integrasi hukum dan ajaran Agama Hindu tumpek wariga dan Perda Nomor 8 Tahun 2019 dapat meningkatkan produksi tanaman padi di Bali, sehingga dapat menjadi strategi ketahanan pangan lokal daerah Bali. Hal ini diketahui sejak diberlakukan Perda tersebut tahun 2020, jumlah produksi beras di Bali terus mengalami kenaikan. Bahkan tahun 2023 mampu memenuhi kebutuhan seluruh warga Bali. Secara praktik, penelitian ini memberi sumbangsih pada harmonisasi hubungan agama dan negara, dan secara teoritis perlu ada penelitian lebih lanjut mengenai teori sistem dalam sistem agama dan negara secara lebih luas.